Warranties, Protection, and Ownership: A Comprehensive Review of Legal Frameworks in the Pre-Owned Car Market in Jharkhand. - Monalisha Ganguly and Dr. Md Saifullah Khalid (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper aims to identify the complex laws governing the pre-owned car market in the state of Jharkhand in India. Taken as a whole, the study makes an insightful appraisal of the legal structure’s antecedent to warranties, consumer laws, and ownership laws while highlighting how the provisions of these structures have impacted the market structures and relations of the used car market. This way, the paper underscores the virtues and vices of these regulations in terms of consumer confidence, market stability, and the general purchase experience. In light of this, the findings will help the consumers, dealers, and legal professionals to be informed on the rights, roles, and legal recourses available about the used car market transactions. The study utilizes data from statutory laws, regulatory policies, and cases within the Jharkhand region and contributes towards understanding ways of boosting consumers’ confidence and encouraging fair trade practices in this sector.